Empowering Batik Bambu Mujur MSMEs with Smart Canting, Production Ergonomics, Digital Management, and Marketing 4.0 - Indah Kurniawati; Yessie Ardina Kusuma; Gita Desipradani; Ridho Akbar (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Bambu Mujur Batik, an Micro, Small, and Medium Enterprise (MSME) producing hand-drawn batik in Sumbermujur Village, faces challenges in production, management, and marketing. Purpose of the study: This Community Developemnt Program aim to solve this enterprise problems by introduced appropriate technology tools and participatory training to strengthen technical and managerial capacities. Methods: Smart canting technology and digital marketing were employed to address production capacity and marketing challenges. In addition, training sessions were conducted to enable participants to effectively use these tools. Training was developed based on participants’ needs and evaluated using pre- and post-tests. Results: Results showed increased knowledge and skills across all modules, with normalized gain values of 0.61–0.84. These improvements enhanced production efficiency, workplace safety, and business digitalization. The outcomes support SDGs 8 and 9, demonstrating that integrating appropriate technologies with participatory training effectively strengthens MSMEs’ competencies and competitiveness.